Identifying barriers to the provision of bystander cardiopulmonary resuscitation (CPR) in high-risk regions: A qualitative review of emergency calls. (August 2018) - Case, Rosalind; Cartledge, Susie; Siedenburg, Josine; Smith, Karen; Straney, Lahn; Barger, Bill; Finn, Judith; Bray, Janet E.
Abstract: Introduction: Understanding regional variation in bystander cardiopulmonary resuscitation (CPR) is important to improving out-of-hospital cardiac arrest (OHCA) survival. In this study we aimed to identify barriers to providing bystander CPR in regions with low rates of bystander CPR and where OHCA was recognised in the emergency call. Methods: We retrospectively reviewed emergency calls for adults in regions of low bystander CPR in the Australian state of Victoria. Included calls were those where OHCA was identified during the call but no bystander CPR was given. A thematic content analysis was independently conducted by two investigators. Results: Saturation of themes was reached after listening to 139 calls. Calls progressed to the point of compression instructions before EMS arrival in only 26 (18.7%) of cases. Three types of barriers were identified: procedural barriers (time lost due to language barriers and communication issues; telephone problems), CPR knowledge (skill deficits; perceived benefit) and personal factors (physical frailty or disability; patient position; emotional factors). Conclusion: A range of factors are associated with barriers to delivering bystander CPR even in the presence of dispatcher instructions – some of which are modifiable. To overcome these barriers in high-risk regions, targeted public education needs to provide information about what occurs in an emergency call, how to recognise an OHCA and to improve CPR knowledge and skills.